The clinical significance of and prospects for the use of biopolymer-based microheterogeneous collagen-containing injectable hydrogel in the therapy of osteoarthritis - I. S. Dydykina; E. V. Arutyunova; P. S. Kovalenko; E. G. Zotkin (Современная ревматология)
The paper gives the current definition of osteoarthritis (OA), which reflects the pathogenetic and clinical characteristics of this disease, as well as general principles for choosing an OA treatment. It describes the effect of glucosamine and chondroitin on the key pathogenetic mechanisms of OA. It is noted that one of the promising areas of therapy for OA is the intra-articular administration of biopolymer-based hydrogels that provide not only an anti-inflammatory, but also regenerative effect that has been experimentally confirmed during their injection into the tendon sheaths. There are data on the efficacy and safety of the Russian drug Sphero®gel, a biopolymer-based microheterogeneous collagen-containing hydrogel that belongs to a class of multicomponent biopolymer-based extracellular matrix mimetics. It consists of the cross-linked farm animal tissue-derived collagen microparticles placed in the gel base. The gel is not only a structural base for collagen microparticles; it also has its own therapeutic potential, since it is structurally similar to the natural extracellular matrix. The drug contains collagen, biologically active components of the extracellular matrix, such as proteoglycans, glycoproteins, uronic acids, growth factors, monosaccharides, and chondroitin sulfate. Extended-release symptomatic agents, Sphero®gel among them, are currently recommended for the treatment of OA. Application of Sphero®gel contributes to increased joint mobility and reduced pain, which allows the limited use of nonsteroidal anti-inflammatory drugs that cause adverse reactions, especially in the presence of comorbid diseases.